Chapter 4 Pretty Dolls Don't Play Dice The Calculated Vulnerabilities of Jennifer Egan's Manhattan Beach (2017) - FERNANDEZ-SANTIAGO, MIRIAM (Taylor & Francis, 2023)
Jennifer Egan's Manhattan Beach (2017) narrates the misadventures of young Irish Catholic Anna Kerrigan in her pursuit of a diving career in the New York docks during WWII. These misadventures are heavily conditioned by the accumulation of a series of structural vulnerabilities intersecting class, gender, religion, immigration, and disability, as well as political and economic corruption, which are emphasized against the backdrop of an impossible American Dream. The structural oppressions visibilized by Egan in this novel will thus serve to reflect on how the purported national invulnerability underlying USA's imperialism in the second half of the 20th century was in fact based on obscuring national vulnerabilities that strongly resonate at the beginning of the new millennium. This chapter explores Egan's formal experimentation with historical fiction as a calculated risk that draws its narrative strengths from the spectacularization of vulnerability while exposing the novel's formal belatedness as a case of vulnerable narrative.